Keterampilan Interpersonal Skill dalam Dunia Kerja - Enny Diah Astuti; Dyan Yuliana; Ali Satri Efendi; Retno Setya Budiasningrum; Rahmi Rosita; Jajang Setiawan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
In the recent complex world of professional work, interpersonal skill improvement is essential. It is more than technical skills, the interpersonal skill demonstrates an employee's ability to understand and respond empathetically to the needs, feelings, and desires of colleagues and superiors in his or her profession. Interpersonal skills also include the ability to solve problems and cope with stress effectively. Given the importance of interpersonal skills in work life, companies should look at for people with strong communication skill who can reinforce a positive work culture. The Participatory Action Research (PAR) method in this activity is used to find out the process or systematic steps used as a means to achieve certain goals effectively. The importance of interpersonal skills in the world of work, that one's success is not only produced because of intelligence and value. There are other things that are no less important needed in our life and socializing in the world of work, namely interpersonal skills possessed by a person.